An Asian poverty line? Issues and options - Stephan Klasen (Asian Development Bank Institute (ADBI), 2016)
Given Asia's record of rapid economic growth and the conceptual and empirical problems of the current international income poverty line ('dollar-a-day'), this paper discusses whether there is merit to develop an Asia-specific poverty line that addresses some of the shortcomings of the dollar-a-day line and additionally considers Asia's particular economic situation. We consider various ways of creating an Asia-specific poverty line, including an Asia-specific international income poverty line (using purchasing-power parity [PPP] adjusted dollars) that is derived from Asian national poverty lines. We argue that there can be some merit in developing an Asian poverty line and that, in the case of income poverty, it would be best to ground such an Asia-specific poverty line in a consistent method of generating national poverty lines using national currencies rather than generating a PPP-adjusted poverty line in international dollars that is specific for Asia. It is important that such a poverty line also considers relative poverty in its assessment to reflect the rising aspirations of Asian societies, in line with suggestions made by Chen and Ravallion (2013) on weakly relative poverty lines. In terms of multidimensional poverty lines, there is also some merit in developing an Asia-specific multidimensional poverty index that takes into account the specific living conditions of Asian societies.
Keywords: 330; Poverty; poverty line; poverty measurement